2022
DOI: 10.1044/2022_jslhr-21-00507
|View full text |Cite
|
Sign up to set email alerts
|

Spelling Errors in French Elementary School Students: A Linguistic Analysis

Abstract: Purpose: This study offers the first description of misspellings across elementary school using the Phonological, Orthographic and Morphological Assessment of Spelling (POMAS), a linguistic framework based on Triple Word Form theory, adapted for French (POMAS-FR). It aims to test the “universality” of POMAS and its suitability to track development in French spelling. Method: One hundred ninety-four typically developing French children (Grades 1–5) produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
2
3
0
Order By: Relevance
“…These data should be enriched by students' verbalizations to make it easier to better understand the choices they made. Lastly, as in other studies (Godin et al, 2018;Plisson et al, 2013), there were very few "inversion" errors even though this type of error was frequently observed in Grade 1 (Joye et al, 2022). This low rate seems to be an indicator of appropriate handling of phonological information.…”
Section: How Do Beginning Writers React To Spelling Fragility Areas?supporting
confidence: 72%
See 4 more Smart Citations
“…These data should be enriched by students' verbalizations to make it easier to better understand the choices they made. Lastly, as in other studies (Godin et al, 2018;Plisson et al, 2013), there were very few "inversion" errors even though this type of error was frequently observed in Grade 1 (Joye et al, 2022). This low rate seems to be an indicator of appropriate handling of phonological information.…”
Section: How Do Beginning Writers React To Spelling Fragility Areas?supporting
confidence: 72%
“…This range of non-standard orthographic forms highlights how important it is for teachers to know the French spelling system so that they can properly interpret what is written, as well as how important it is for students to acquire not only phonological and orthographic skills but also morphological skills in order to produce words in Grade 1. As in the study by Joye et al (2022), it was also demonstrated that orthographic variations are predominant in first grade. They result in numerous substitutions (confusion with another grapheme) that can reflect a plausible choice of grapheme (en instead of an) or a simpler choice (o instead of au).…”
Section: How Do Beginning Writers React To Spelling Fragility Areas?supporting
confidence: 65%
See 3 more Smart Citations